Nursing students' knowledge, willingness, and attitudes toward the first aid behavior as bystanders in traffic accident trauma: A cross-sectional survey - Li Pei; Fangfang Liang; Shiquan Sun; Hongwu Wang; Haoying Dou (Elsevier, 2019)
Objectives: The purpose of the study was to investigate the nursing students' levels of the knowledge, willingness, and attitudes toward first aid behavior as bystanders in road traffic accident and the related factors. Methods: A total of 475 nursing students were recruited by convenience choosing in Tianjin University of Traditional Chinese Medicine. The nursing students' self-efficacy, core self-evaluation, knowledge, willingness and attitudes toward first aid behavior as bystanders in traffic accidents were investigated with a self-designed questionnaire. Results: The scores of knowledge, willingness, and attitudes toward first aid behavior in traffic accident trauma were 7.51 ± 1.93, 15.54 ± 5.03, and 7.73 ± 1.56, respectively. Students who once gained training of first aid showed lower levels of attitude toward first aid behavior than those untrained (t = −2.345, P = 0.019). It was found that self-efficacy was correlated to the knowledge (r = 0.150, P < 0.001), willingness (r = 0.182, P < 0.004) and attitudes toward behavior of the first aid (r = 0.371, P < 0.001) among nursing students. Core self-evaluation was correlated to knowledge (r = 0.193, P < 0.001) and attitudes toward behavior of the first aid (r = 0.199, P < 0.001). Conclusions: The first aid knowledge among nursing students was not satisfactory. The study suggested that an unsustainable short first-aid training program may bring negative effects. Countermeasures should be taken to ensure both quality and continuity of first aid training. Meanwhile, more attention should be paid to improving the self-efficacy and core self-evaluation of the nursing students. Keywords: Attitude, Accidents, Traffic, First aid, Knowledge, Self-assessment, Self- efficacy, Students, Nursing